SYNTHESIS AND CHARACTERIZATION OF SUPERIONIC CONDUCTING GLASSES (AgI)x(Ag2S)x(AgPO3)1-2x - D. Sulistyanintyas; Evvy Kartini (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2006)
SYNTHESIS AND CHARACTERIZATION OF SUPERIONIC CONDUCTING GLASSES (AgI)x(Ag2S)x(AgPO3)1-2x. Samples of Superionic Conducting Glasses (AgI)x(Ag2S)x(AgPO3)1-2x with x = 0, 0.09, 0.17, 0.23, 0.33, 0.37, 0.41 and 0.44 have been synthesized by rapid quenching method. Some physical properties including crystal structure, thermal behavior, ionic conductivity and transference number have been characterized and measured by using respectively, an X-Ray Diffractometer (XRD), a Differential Scanning Calorimetric (DSC), and an Impedance Spectroscopy (LCR-meter). The diffraction patterns of (AgI)x(Ag2S)x(AgPO3)1-2x for all compositions of x show only one broad peak indicating that all the samples are good glasses and have an amorphous structure. In general the glass transition temperature Tg, decreases from 398oC to 275 oC as x increases. The results of ionic conductivity (s) measured at various frequencies and voltages show a significant increase as x increases.The maximum ionic conductivities are obtained for x=0.44 at different voltages s(0.5 volt)=1.66x10-2 S/cm, s(1 volt)=1.91x10-2S/cm, s(2 volt)=2.34x10-2 S/cm, while the ionic conductivities for un-doped glass AgPO3 are s(0.5 volt)=9.33x10-8S/cm, s(1 volt)=1.17x10-7S/cm, s(2 volt)=1.55x10-7 S/cm. The transference number, tion is approximate to 1 indicating that the conduction is essentially ionic in nature.